The Effect of Smartphone Features on Customer Engagement: The Mediating Role of Brand Value - Ahmet Songur (Mehmet Akif Ersoy Üniversitesi İktisadi ve İdari Bilimler Fakültesi Dergisi)
AbstractThe continuous increase in the use of smartphones and the rapid growth in the demand for these devices increase the interest in the subject. The smartphone market has attracted the attention of many businesses due to the increasing usage rates and has resulted in new brands and models joining the competition in the market. This research aims to examine the relationships between smartphone features, customer engagement, and brand value in the context of Turkish smartphone users. For this purpose, a theoretical model is proposed to encompasses the interactions between these variables. The model is tested by analyzing the data obtained from 726 Turkish smartphone users. The findings reveal that smartphone features have a strong influence on brand value and brand value has a strong influence on customer engagement. Smartphone features alone do not affect customer engagement. On the other hand, brand value is found to mediate the relationship between smartphone features and customer engagement.